Aplikasi wedding planner dan analisis kelayakan guna meningkatkan income generating badan pengelola usaha Universitas Jambi - Agus Syarif; Ahmad Nur Budi Utama; Idham Khalik; Istiqomah Malinda SB (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Universitas Jambi as a State University with the status of a Public Service Entity (BLU) has two sources of income generating, namely those from academic services and non-academic services (academic support services). The implementation of academic support services is entrusted to the Business Management Agency (Badan Pengelola Usaha). BPU is tasked with carrying out the development of business units and optimizing the acquisition of university funding sources. Based on this task, BPU established the Weddy Feast business unit under the Commercialization and Services department. This research analyzes the business feasibility of wedding planner to increase income generating of the Business Management Agency. The conduct interviews and surveys some vendors in 43 types of business. The results show that the establishment of Weddy Feast able to optimize the potential of university assets involving 43 types of businesses and 15 of them can be managed by students in creating student entrepreneurs in the context of implementing Merdeka Belajar Kampus Merdeka (MBKM) program of the Ministry of Education, Culture, Research and Technology, which is strengthened by realizing the UNJA Smart platform with digital transformation elements in the real business world, in the form of making a weddy feast application.  The Net Present Velue (NPV) of wedddy planner is positive, Rp.577.049.066,-  and Internal Rate of Return (IRR) 156,12% hingher than weighted average cost of capital (WACC) 12%.